Malva sylvestris derivatives as inhibitors of HIV-1 BaL infection. Issue 6 (19th March 2021) - Benso, Bruna; Rosalen, Pedro Luiz; Pasetto, Silvana; Marquezin, Maria Carolina Salomé; Freitas–Blanco, Verônica; Murata, Ramiro Mendonça
Abstract: The emphasis of the present study is to evaluate a natural product and the potential microbicide activity using a dual chamber infection method. Malva sylvestris extracts and fractions were screened for anti-HIV activity by measuring the virus-antibody neutralization. Plant extracts with strong antiviral activity working in nanomolar or picomolar range can be used to enhance the activity of synthetic compounds and work as anti-HIV agents. The aqueous fraction (AF) of M. sylvestris demonstrated antiviral activity in a model with epithelial and blood cell lines. The AF showed an effective antiviral potential on the TZM-bl cells with reduction scores higher than 60% of infectivity. Quantification of p24 in the supernatant of the co-culture model demonstrated a reduction in the number of viral particles after AF treatment ( p < 0.05). Cytokines were quantified and all signaling inflammatory markers; IL1-alpha, IL-beta, IL-6, IL-8 and GM-CSF ( p < 0.05) were modulated by positive control and AF treatments. In particular, IL-6 had lower levels of expression in Malva groups when compared to the Zidovudine positive control group. Natural occurring derivatives of M. sylvestris demonstrated to work inhibiting reverse transcriptase enzyme action. M. sylvestris contains highly potential anti-HIV-1 BaL components and may be considered a potential source for new formulations in the development of topical microbicides. Abstract :